Auf dem Weg zur neuen globalen Kompetenzaufteilung? Zur Internationalisierung von Entwicklung und Konstruktion in der deutschen Automobilzulieferung - Fuchs, Martina (ERDKUNDE, 2003)
Internationalization of manufacturing industries is usually discussed with regard to labour-intensive production. This paper analyses the internationalization of know-how intensive parts of the manufacturing industry and focuses on engineering. The question of internationalization of engineering tasks is discussed for the automobile components supply industry. The main topic is the governance in multinational companies which is important for the international division of competences in engineering of the companies. The study shows that the German automobile components supply companies are proceeding cautiously on the path of internationalization. The companies that have already introduced an international division of competences do not necessarily have losses of competences in their centres, because new capacities are created, i.e. the skills of steering the engineering process. However, there may be processes of learning, or upgrading, in peripheral plants, too. The study shows that in multinational companies governance seldom means direct control in the multinational companies; rather, it can be characterized by interdependencies of power, and this offers possibilities to plants in the Newly Industrializing Countries.